Freight on urban public transportation: A systematic literature review. (December 2022) - Elbert, Ralf; Rentschler, Johannes
Abstract: Public transportation offers a promising opportunity for freight transportation in urban areas. Through the sharing of infrastructure, vehicles, or even space inside wagons, synergies can be realized which can lead to a more efficient and environmentally-friendly transportation of goods in cities. This paper conducts a comprehensive investigation of the state-of-the-art of freight on public transportation by means of a systematic literature review. We start by giving an overview of the various ways in which freight on public transportation can be realized. Then we analyze the identified references, classified into qualitative and quantitative approaches, regarding methodology, mode of transportation, shared aspects, underlying network, and utilized data. We find that freight on urban public transportation is a highly dynamic and diverse research field. Finally, we describe opportunities and barriers for freight on public transportation and identify the main fields for future research, among others the further inclusion of external costs and the more frequent application of stochastic and real-time data.